Методологічно відправні поняття відносно правових видів таємниці - Олійник, В.; Olijnyk, V. (Східноєвропейський національний університет імені Лесі Українки, 2016)
У статті за допомогою термінологічного та есенційного аналізу з’ясовується, яке поняття є відправним стосовно юридичних видів таємниць, оскільки це має значення для вірного тлумачення і застосування термінології у різних галузях права. Одночасно окреслюється теоретичні правовий, філософський, філологічний та соціальний аспекти, виокремлюються суттєві правові ознаки таємниці.The article reveals which concepts are fundamental for the legal types of secrecy employed by various branches of law, in particular: «state secret», «personal privacy», «medical secrecy», «commercial secrecy», etc. The argues his opinion by claiming that all these legal terms are a generic concept of secrecy, the foundation of which, in its turn, is the concept of information (knowledge/statements). In the focus of attention are legal, philosophical, philological and social aspects of the concept of secrecy and the article highlights its basic legal characteristics. The above mentioned in the article terminological and the essential analysis of the concept of secrecy makes it possible to use the concept of information as a methodological starting point in determining the types of legal secrets. Further use of such approaches synthesis provides clues to understanding of what distinguishes one kind of secrecy from the other legal secrecies in view of information concept.
Methodological Fundamental Concepts of the Legal Forms of Secrecy
Keywords: інформація; таємниця; правові види таємниць; правова наука; юридичний термін; есенційний підхід; методологія дослідження; information; secret; legal types of secrecy; essential approach; research methodology